Estimation of aggregate size of red blood cell by introducing reference power spectrum measured for hemispherical ultrafine wire. (1st July 2022) - Higashiyama, Kyohei; Mori, Shohei; Arakawa, Mototaka; Yashiro, Satoshi; Ishigaki, Yasushi; Kanai, Hiroshi
Abstract: Noninvasive measurement of the degree of red blood cell (RBC) aggregation is useful for evaluating blood properties. In the present paper, we proposed a method to estimate the size of RBC aggregates without using the power spectrum of the posterior wall by introducing a reference scattering spectrum. The reference power spectra were calculated using the power spectrum measured for an ultrafine wire with a hemispherical tip. They were applied to the size estimation of microparticles simulating RBC aggregates. The estimated sizes were close to the true values, which shows that the calculated reference power spectra were suitable for accurate size estimation. The proposed method was also applied to in vivo measurements, and the estimated sizes between at rest and in RBCs aggregated by avascularization were successfully differentiated. This demonstrates that the proposed method will be useful for estimating the size of RBC aggregates.